Depression Is Associated With the Absence of Sex Differences in the 2D:4D Ratio of the Right Hand - Sanwald, Simon; Widenhorn-Müller, Katharina; Wernicke, Jennifer; Sindermann, Cornelia; Kiefer, Markus; Montag, Christian (Frontiers in Psychiatry, 2019)
The 2D:4D digit ratio reflects prenatal testosterone relative to estradiol exposure of the developing embryo. Relatively higher levels of prenatal testosterone have been related to lower 2D:4D ratios. In addition, higher 2D:4D ratios have been associated with female gender, neuroticism and depression severity. Therefore, the present study investigated whether 2D:4D ratios differ between inpatients with major depression and matched healthy controls and whether 2D:4D ratios correlate with depression severity. We examined 139 inpatients diagnosed with major depression according to DSM-IV criteria and 137 healthy controls regarding 2D:4D ratios of both hands and BDI-II scores. While we observed significant sex differences in the 2D:4D ratio of the right hand in the healthy control group (women on average showed a significantly higher 2D:4D ratio), no such differences were found in the group of depressed patients. The 2D:4D digit ratios did not correlate with depression severity even when examined for group and sex separately. We conclude that major depression is associated with an absence of sex differences in the 2D:4D ratio.